Lustrzany świat sportowców - user experience platformy treningowej Zwift w świetle badań - Jaskowska, Bożena (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The main assumptions of the mirror world were presented in this paper, with particular emphasis on the sports environment and the Zwift application as a mixed reality platform. The service was characterised and an analysis of the impressions and experiences of users - people practising cycling in the real and virtual world - was carried out. The method of source analysis as well as a diagnostic survey in the form of an in-depth interview and a questionnaire were applied. The research shows that users, regardless of their sport’s goal and skill, meet their needs as a result of using the application and highly evaluate the level of immersion, interactiveness and virtuality. Supporting and extending traditional training, saving time and diversifying exercise with options not available in the real world are the most common reasons for using the application. The functionalities reflecting traditional cycling in the digital world are assessed at a good and very good level. Among the biggest flaws of the application are user fraud and cyber errors. The analysis of research and literature on the subject leads to the conclusion that the merging of the real and virtual worlds will increase, which will ultimately lead to the creation of a mirror world.